Risk Assessment of RYR Food Supplements: Perception vs. Reality - Righetti, Laura; Dall'Asta, Chiara; Bruni, Renato (Frontiers in Nutrition, 2021)
Thirty-seven red yeast rice (RYR) food supplements were screened for their mycotoxin and natural statin content. Products included pure RYR capsules and multi-ingredient formulations with standardized amounts of monacolin K (MK), marketed both online and retail in the European Union. In terms of mycotoxins, citrinin (CIT) was found in all the monitored products. As CIT content ranged from 100 to 25100 µg/kg, only four products were compliant with maximum EU levels in force until April 2020, while a single product was compliant with the limit of 100 µg/kg introduced after that date. Four contaminated products were labeled as “citrinin free”. In terms of natural statins, nine products had a lower content versus label statements (from -30% to -83%), while for 24 a larger MK amount (from 10 to 266%) was noticed. Three products had a negligible MK content and only 19 offered a daily dosage exceeding 10 mg as dictated by the health claim granted by EFSA in the EU. No sample had label values compliant with pharmaceutical Good Manufacturing Practices requirements (95–105% content of active constituent). Variable, but small amounts of simvastatin (0.1-7.5 µg per daily dose) were found in 30 samples. These results suggest that limited efficacy and reported safety issues may stem from an underregulated and undercontrolled market, weakening both effectiveness and risk assessment evaluations.